KONSEP Al-ḤUBB AL-ILĀHĪ: STUDI ANALISIS TERHADAP PEMIKIRAN IBN ‘ARABĪ DALAM KITAB AL-FUTŪḤĀ ALMAKKIYYAH - Nihayatul Husna; Husna, Nihayatul (STAI Syubbanul Wathon Magelang, 2022)
This study focuses on analyzing the term ḥubb in the Al-Futūḥāt Al-Makkiyyah. This is a crucial term because, from the perspective of Ibn ‘Arabī, ḥubb is a maqām ilāhi, which is not limited to material things. According to him, love of God (alḥubb al-ilāhī) requires two foundations of love, namely, natural love (al-ḥubb aṭ-ṭabī’ī) and spiritual love (al-ḥubb arrūḥānī). This study aimed to find the meaning of al-ḥubb al-ilāhi from the perspective of Ibn ‘Arabī. The research method employs library research by constructing al-Futūḥāt al-Makkiyyah by Ibn ‘Arabī as the object of study. Starting with tracing all the term ḥubb in the Al-Futūḥāt Al-Makkiyyahas a seminal concept, conducting language studies, mapping out the interpretations, and reviewing the results of studies, then formulating concepts related to the issues being raised. This study reveals four important points of the concept of alḥubb al-ilāhi from the perspective of Ibn ‘Arabī, namely ḥubb as the cause of the existence of the universe, māqāmat ḥubb, three forms of ḥubb, conditions of al-ḥubb al-ilāhi. These four points, in addition to describing the concept of al-ḥubb al-ilāhi Ibn ‘Arabī, also provide a new understanding of the meaning of the word ḥubb, which has changed conceptual meaning. When mentioning the word ḥubb, what appears is an understanding that refers to the form of obedience to Allah and His Messenger